The Influence of Job Autonomy, Trust in Management, and Work Meaningfulness on Psychological Empowerment in Digital Startups - Riesna Apramilda; Enny Diah Astuti; Desi Kristanti; Haris Karyadi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
The present research aims to investigate the influence of job autonomy, trust in management and work meaningfulness on psychological empowerment of the employees working in digital startups. The rationale for this research is that the digital startup sector has very high expectations regarding ability to adapt and generate ideas, which means that the employee should have the empowerment of the psychological empowerment factor to the fullest extent. The research adopts a quantitative explanatory approach, and a questionnaire is the tool used to collect data from the 150 digital startup employees who are selected by purposive sampling. Data are analyzed by multiple linear regression after validating, checking reliability, and testing classical assumptions for data. The results show that job autonomy, trust in management and work meaningfulness are positively related to psychological empowerment and this relationship is significant. The present research offers a significant contribution to the literature on organizational behavior in a theoretical sense, as it reveals the factors that shape psychological empowerment within the digital startups context. Through the practical implications of the study, managers will have the necessary guidance to establish a work climate that facilitates employee psychological empowerment, thereby leading to enhanced performance and sustainability of the organization.